Free Fatty Acids Extraction from Crude Rice Bran Oil with Isopropyl Alcohol - Febrianto Situmorang (13014059), Ivan Wijaya Husada (13014099) , Ricky
Rice is the most important carbohydrate sources in Indonesia. In Indonesia, local rice production reaches 75,36 million tons. Accordingly, Indonesia also produce around 5,652 million tons of rice bran. Currently, rice bran is usually utilized as feed stock in Indonesia. Economically, and nutritionally, the potential of rice bran oil is immense since it contains 10% of healthy fats. Rice bran oil is also one of the healthiest vegetable oil as it contains not only nutrients, but also good minerals antioxidants such as γ-oryzanol, tocopherol, and tocotrienols. Even though rice bran oil has immense health benefits and huge market potential, the high content of free fatty acids (FFA) in crude rice bran oil is proven to be the main culprit behind its low market. Due to the activity of lipase in rice bran, crude rice bran oil usually contains free fatty acid in high concentration (2,74-14,15 meq O2/kg). Saponification is conventionally used to deacidify rice bran oil. However, this method results in high losses of neutral oil, produced a large amount of waste, and reduce antioxidant content in rice bran oil. Solvent extraction using short chains alcohols are being considered as alternatives for saponification. In this case, isopropyl alcohol is used as the main solvent as it is relatively stable, cheap and have a higher boiling point compared to ethanol. As physical extraction could only deliver a limited amount of FFA, a hybrid extraction is needed. A limited amount of potassium hydroxide is used to react more FFA from oil rich phase. Thus, the extraction could be done more efficiently. This research will be done in two main phases. The first one is to develop distribution coefficient from IPA-FFA system that will be used for liquid-liquid equilibrium. The second phase is to extract FFA in a batch stirred tank. The feed of this extraction is a mixture of rice bran oil and free fatty acid while the solvent is a mixture of isopropyl alcohol and water. For physical equilibrium, the distribution coefficient is around 0,55 to 0,87. However, this number is increased to 0,92 to 1,2 for hybrid equilibrium. Those number, however is for hybrid equilibrium without considering the amount of FFA which reacted with potassium hydroxide. If those amount of FFA is considered, the distribution coefficient is hugely increased, to 1,4 to 45. The equilibrium time for hybrid extraction is around 10 minutes.